The Effect of Reward and Punsihment on Students' Discipline in Performing Congregations - Ahda Fitri; Ahmad Lahmi; Syaflin Halim (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M) Sekolah Tinggi Agama Islam As-Sunnah, 2020)
This research is set against the backdrop of the low awareness of some students in obeying the discipline of praying zuhur congregations, as well as there are still students who are late in praying zuhur congregations, and some students who choose to receive sanctions or punishments rather than perform the prayer of zuhur congregation. In accordance with the above problems the purpose of the study is: 1) Describe the level of influence of awards on the discipline of the implementation of prayer zuhur congregation, 2) the effect of sanctions on the discipline of the implementation of zuhur prayer of 1st State Luhak Nan Duo. In accordance with typical data in this study used quantitative approach, research data is obtained through questionnaires. The findings were analyzed with correlation techniques, in unison, and Regression Coefficient Determination Test and Regression Coefficient t test. The results of the analysis showed that the: first influence of the Award (X1) on the discipline of the implementation of zuhur prayer congregation (Y) at a rate of 5 % with the hypothesis was found 2,042, while at the level of 1 % there was no effect of the award ( X1) on the discipline of the implementation of zuhur prayer congregation (Y), while independently the award was influential by 10%. Second, there is the effect of sanctions on the discipline of the implementation of zuhur prayer congregation both at the level of 5 % and 1 % with the hypothesis found 2,732, while the sanction independently affects 25.5%